Using Critical Discourse Analysis for understanding knowledge construction in English pedagogy - Sharma, Bal Krishna (Bodhi: An Interdisciplinary Journal, 2013)
This paper makes an attempt to make a better understanding of expert-teacher interactions through an examination of discursive practices by native English speaking ‘expert’ and English teachers from Asia. I analyzed ten online interaction events with an aim to scrutinize the construction of knowledge and expertise among in an unfolding interaction, and looked particularly into claims of expertise, participants’ positioning and identity in these virtual interactions, and any hierarchical differences in their discourses that result from the power differences between the ‘expert’ and the participating teachers. In order to analyze the data, I used the critical discourse analysis (CDA) framework and draw insights from critical pedagogy. The analysis shows that the ‘expert’, positioned as the authority of knowledge, suggested solutions to challenges that the teachers in different parts of world are facing, and also articulated his view of good pedagogical practices. The analysis also reveals that the expert’s pedagogical ideologies at times compete and contrast with those of the teachers. The study, therefore, questions the effectiveness of the taken-for-granted pedagogical theories and practices from the native English speaking professionals for the teachers in the periphery countries and suggests that teachers in the receiving end need to critically evaluate appropriateness of such pedagogical practices taking consideration of the local teaching/learning contexts. Bodhi: An Interdisciplinary Journal, 5, 2011, Page 53-79 DOI: http://dx.doi.org/10.3126/bodhi.v5i1.8045